Intrinsically stretchable fully π-conjugated polymer film via fluid conjugated molecular external-plasticizing for flexible light-emitting diodes - Zhiqiang Zhuo; Mingjian Ni; Ningning Yu; Yingying Zheng; Yingru Lin; Jing Yang; Lili Sun; Lizhi Wang; Lubing Bai; Wenyu Chen; Man Xu; Fengwei Huo; et al. (Nature Communications, 2024)
Abstract Fully π-conjugated polymers with rigid aromatic units are promising for flexible optoelectronic devices, but their inherent brittleness poses a challenge for achieving high-performance, intrinsically stretchable fully π-conjugated polymer. Here, we are establishing an external-plasticizing strategy using semiconductor fluid plasticizers (Z1 and Z2) to enhance the optoelectronic, morphological, and stretchable properties of fully π-conjugated polymer films for flexible light-emitting diodes. The synergistic effect of hierarchical structure and optoelectronic properties of Z1 in poly(9,9-di-n-octylfluorene-alt-benzothiadiazole) (F8BT) films enable excellent stretchable deformability (~25%) and good conductivity. PLEDs based on F8BT/Z1 films show stable electroluminescence and efficiency under 15% stretch and 100 cycles at 10% strain, revealing outstanding stress tolerance. This strategy is also improving the stretchable properties of polymers like poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PFO) and poly(2-methoxy-5(2′-ethyl)hexoxy-phenylenevinylene) (Super Yellow), demonstrating its general applicability. Therefore, this strategy can provide effective guidance for designing high-performance stretchable fully π-conjugated polymers films for flexible electronic devices.